Modelling Religion and Nationalism on a Godly-Civil Continuum - Lewin, Eyal; Bick, Etta (European Scientific Journal, ESJ, 2017)
There is no precise distinction between traditional godly religion and civil secular religion; both phenomena are in fact quite similar. This is an odd statement to present almost fifty years after Robert Bellah's momentous "Civil Religion in America" and a century and a half after Rousseau coined the term civil religion. In order to explain this assertion, we will begin our discussion of civil religion by placing it in its broader context, that of religion itself. Recognizing its capacity to mobilize human resources like no other social mechanism, religion is first of all defined, and its essential characteristics are outlined. When examining the attributes of religion, we shall find that many of these same characteristics are typical of nationalism and patriotism as well. In order to distinguish between religion and these ostensibly secular phenomena we propose a godly-civil continuum, which maps and compares traditional and civil religions and the nexus between them. We suggest that these seemingly different phenomena share a common prototype and differ only in the degree to which godly authorities or civil authorities gain dominance one over the other in a particular political system.